2021
DOI: 10.1093/ajcn/nqaa274
|View full text |Cite
|
Sign up to set email alerts
|

Very low ileal nitrogen and amino acid digestibility of zein compared to whey protein isolate in healthy volunteers

Abstract: Background Whey protein and zein are of nutritional interest due to their high leucine content, but little data are available on their amino acid (AA) ileal digestibility. Objective This study aimed to determine ileal digestibility of whey protein isolate (WPI) and zein in healthy volunteers by use of the naso-ileal intubation method, which allows continuous collection of postprandial ileal digesta. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
5
26
1
Order By: Relevance
“…It appears that for spirulina, which has a digestibility 12–15% lower than that of the other two proteins, the data dispersion is dramatically expanded. We observed the same in humans, for instance, concerning zein digestibility, which was the lowest we observed among our intestinal tube studies [ 8 ▪ ]. The SD was 13% (for a mean of 60%), with the lowest individual value being 39% and the highest 82%.…”
Section: Determinants Of Amino Acid Bioavailability From Ingested Prosupporting
confidence: 72%
See 3 more Smart Citations
“…It appears that for spirulina, which has a digestibility 12–15% lower than that of the other two proteins, the data dispersion is dramatically expanded. We observed the same in humans, for instance, concerning zein digestibility, which was the lowest we observed among our intestinal tube studies [ 8 ▪ ]. The SD was 13% (for a mean of 60%), with the lowest individual value being 39% and the highest 82%.…”
Section: Determinants Of Amino Acid Bioavailability From Ingested Prosupporting
confidence: 72%
“…Measuring ileal digestibility is complex and requires invasive procedures, depending on the model. In humans, intestinal tubing allows for the continuous collection of effluents and adequate measurements of ileal amino acid losses [ 8 ▪ ]. However, this method is very invasive and ileostomized patients have therefore been used as convenient alternative due to the direct access to digesta.…”
Section: Methodological Considerations For Measuring Amino Acid Bioavmentioning
confidence: 99%
See 2 more Smart Citations
“…or have a protein structure resistant to hydrolysis. However, with some exceptions ( 35 ), real ileal digestibility studies in humans have reported high digestibility estimates for plant protein isolates (89–92%) that are comparable to those of meat or egg proteins (90–94%) ( 3 ). Indeed, isolate extraction processes can reduce or suppress the activity of antinutritional factors ( 36 38 ) and preparation processes (such as heating) can often markedly improve protein resistance to hydrolysis via protein denaturation ( 29 ).…”
Section: Discussionmentioning
confidence: 99%